A role for amyloid precursor protein translation to restore iron homeostasis and ameliorate lead (Pb) neurotoxicity. Issue 3 (August 2016) - Rogers, Jack T.; Venkataramani, Vivek; Washburn, Cecilia; Liu, Yanyan; Tummala, Vinusha; Jiang, Hong; Smith, Ann; Cahill, Catherine M.
Abstract: Iron supplementation ameliorates the neurotoxicity of the environmental contaminant lead (Pb); however, the mechanism remains undefined. Iron is an essential nutrient but high levels are toxic due to the catalytic generation of destructive hydroxyl radicals. Using human neuroblastoma SH‐SY5Y cells to model human neurons, we investigated the effect of Pb on proteins of iron homeostasis: the Alzheimer's amyloid precursor protein (APP), which stabilizes the iron exporter ferroportin 1; and, the heavy subunit of the iron‐storage protein, ferritin (FTH). Lead (Pb(II) and Pb(IV) inhibited APP translation and raised cytosolic iron(II). Lead also increased iron regulatory protein‐1 binding to the cognate 5′untranslated region‐specific iron‐responsive element (IRE) of APP and FTH mRNAs. Concurrent iron treatment rescued cells from Pb toxicity by specifically restoring APP synthesis, i.e. levels of the APP‐related protein, APLP‐2, were unchanged. Significantly, iron/IRE‐independent over‐expression of APP695  protected SH‐SY5Y cells from Pb toxicity, demonstrating that APP plays a key role in maintaining safe levels of intracellular iron. Overall, our data support a model of neurotoxicity where Pb enhances iron regulatory protein/IRE‐mediated repression of APP and FTH translation. We propose novel treatment options for Pb poisoning to include chelators and the use of small molecules to maintain APP and FTH translation. We propose the following cascade for Lead (Pb) toxicity to neurons; by targeting the interaction between Iron regulatory protein‐1 and Iron‐responsive elements, Pb caused translational repression of proteins that control intracellular iron homeostasis, including the Alzheimer's amyloid precursor protein (APP) that stabilizes the iron exporter ferroportin, and the ferroxidase heavy subunit of the iron‐storage protein, ferritin. When unregulated, IRE‐independent over‐expression of APP695 protected SH‐SY5Y neurons from Pb toxicity. There is a novel and key role for APP in maintaining safe levels of intracellular iron pertinent to lead toxicity. Abstract : We propose the following cascade for Lead (Pb) toxicity to neurons; by targeting the interaction between Iron regulatory protein‐1 and Iron‐responsive elements, Pb caused translational repression of proteins that control intracellular iron homeostasis, including the Alzheimer's amyloid precursor protein (APP) that stabilizes the iron exporter ferroportin, and the ferroxidase heavy subunit of the iron‐storage protein, ferritin. When unregulated, IRE‐independent over‐expression of APP695 protected SH‐SY5Y neurons from Pb toxicity. There is a novel and key role for APP in maintaining safe levels of intracellular iron pertinent to lead toxicity.